2002 IEEE International Solid-State Circuits Conference. Digest of Technical Papers (Cat. No.02CH37315)
DOI: 10.1109/isscc.2002.992937
|View full text |Cite
|
Sign up to set email alerts
|

A 175 mV multiply-accumulate unit using an adaptive supply voltage and body bias (ASB) architecture

Abstract: Traditionally, V dd scaling has been one of the most effective ways to reduce operating power, with the device leakage component being much smaller than the dynamic switching component. In applications where the operating frequency changes, dynamic voltage (and frequency) scaling (DVS) has been widely explored to minimize power dissipation [1][2][3]. The basic notion is to scale the supply voltage and stretch out the computation to the maximum available time as the processing rate is changed. The lower limit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Both are proactive techniques, where the target is to track the delay of a real critical path with some added margin. The replica circuit can either be on the actual path [4] or it can consist of a collection of digital gates with tunable delays [5]. The latter is referred to as tunable replica circuit, and can be tuned on chip to match the delay of the critical path.…”
Section: B Timing Marginsmentioning
confidence: 99%
“…Both are proactive techniques, where the target is to track the delay of a real critical path with some added margin. The replica circuit can either be on the actual path [4] or it can consist of a collection of digital gates with tunable delays [5]. The latter is referred to as tunable replica circuit, and can be tuned on chip to match the delay of the critical path.…”
Section: B Timing Marginsmentioning
confidence: 99%
“…Furthermore, dynamic logic provides high-speed operation for circuits which are operating at nominal supply voltage. However, it has several disadvantages in ultra-low-voltage operation [45]. Because of the low supply level at which the output will be precharged, only a small amount of charge is stored on the dynamic node.…”
Section: Dynamic Logicmentioning
confidence: 99%
“…Previous work demonstrated that body biasing and DVFS implemented independently can achieve lower power than DVFS alone [5]. In this implementation, the processor specifies frequency and VDD while a body bias controller adjusts the body biases to meet the frequency target.…”
Section: Related Workmentioning
confidence: 99%